Higher dynamic medial knee load predicts greater cartilage loss over 12 months in medial knee osteoarthritis - Bennell, Kim L; Bowles, Kelly-Ann; Wang, Yuanyuan; Cicuttini, Flavia; Davies-Tuck, Miranda; Hinman, Rana S (Annals of the rheumatic diseases, 2011)
Objective Mechanical factors, in particular increased medial knee joint load, are believed to be important in the structural progression of knee osteoarthritis. This study evaluated the relationship of medial knee load during walking to indices of structural disease progression, measured on MRI, in people with medial knee osteoarthritis. Methods A longitudinal cohort design utilising a subset of participants (n=144, 72%) enrolled in a randomised controlled trial of lateral wedge insoles was employed. Medial knee load parameters including the peak knee adduction moment (KAM) and the KAM impulse were measured at baseline using three-dimensional gait analysis during walking. MRI at baseline and at 12 months was used to assess structural indices. Multiple regression with adjustment for covariates assessed the relationship between medial knee load parameters and the annual change in medial tibial cartilage volume. Binary logistic regression was used for the dichotomous variables of progression of medial tibiofemoral cartilage defects and bone marrow lesions (BML). Results A higher KAM impulse, but not peak KAM, at baseline was independently associated with greater loss of medial tibial cartilage volume over 12 months (β=29.9, 95% CI 6.3 to 53.5, p=0.01). No significant relationships were seen between medial knee load parameters and the progression of medial tibiofemoral cartilage defects or BML. Conclusion This study suggests knee loading, in particular the KAM impulse, may be a risk factor for loss of medial tibial cartilage volume. As knee load is modifiable, load-modifying treatments may potentially slow disease progression.